Pengaruh Disiplin Kerja, Keselamatan Kerja, dan Kesehatan Kerja Terhadap Produktivitas Kerja Karyawan di UD Mugi Lestari Papar - Diana Ayu Pramesti; Sonny Subroto Maheri L; Nuril Aulia Munawaroh (FEB Universitas Maritim Semarang, 2023)
Human resource management is an important aspect in the business world, in a company the potential of human resources will determine the direction in achieving a goal set by the company. This study explains the effect of work discipline, occupational safety and occupational health on the work productivity of UD Mugi Lestari Papar employees. The number of samples taken in this study was 33 employees. In this study, it was found that work discipline had a partial and significant effect on employee work productivity, work safety had a partial and significant effect on employee work productivity and occupational health had a partial and significant effect on employee work productivity. Furthermore, work discipline, occupational safety and occupational health have a silmutant and significant effect on employee work productivity.